Transmission pathways and mediators as the basis for clinical pharmacology of pain. Issue 10 (2nd October 2016) - Kirkpatrick, Daniel R.; McEntire, Dan M.; Smith, Tyler A.; Dueck, Nicholas P.; Kerfeld, Mitchell J.; Hambsch, Zakary J.; Nelson, Taylor J.; Reisbig, Mark D.; Agrawal, Devendra K.
ABSTRACT: Introduction : Mediators in pain transmission are the targets of a multitude of different analgesic pharmaceuticals. This review explores the most significant mediators of pain transmission as well as the pharmaceuticals that act on them. Areas covered : The review explores many of the key mediators of pain transmission. In doing so, this review uncovers important areas for further research. It also highlights agents with potential for producing novel analgesics, probes important interactions between pain transmission pathways that could contribute to synergistic analgesia, and emphasizes transmission factors that participate in transforming acute injury into chronic pain. Expert commentary : This review examines current pain research, particularly in the context of identifying novel analgesics, highlighting interactions between analgesic transmission pathways, and discussing factors that may contribute to the development of chronic pain after an acute injury.